Pendampingan Implementasi Deep Learning Berbantuan Artificial Intelligence Dalam Menyiapkan Pendidik Unggul Sekolah Dasar Kabupaten Temanggung - Puguh Ardianto Iskandar; Galih Cahya Pratama; Muhamad Afandi; Jupriyanto; Andi Maulana (Inisiatif : Jurnal Dedikasi Pengabdian Masyarakat, 2026)
The development of artificial intelligence (AI) requires elementary school teachers to be competent in integrating technology with meaningful learning. However, teachers under the auspices of the Temanggung Regency Education Office still face limited understanding of Deep Learning and the use of AI in learning. This community service activity aims to improve teacher competency in implementing AI-assisted Deep Learning. The program was implemented in January 2026 with the involvement of 50 elementary school teachers using a Participatory Action Research (PAR) approach. Activities included awareness raising, training, continuing education, and mentoring. Evaluation was carried out through pre-tests and post-test, observations, participant reflections, and assessments of learning products. The results of the activity showed an increase in teacher competency from 47.25% to 89.00%. In addition, all participants successfully produced AI-assisted Deep Learning-based learning tools in the form of teaching modules, student worksheets (LKPD), digital learning media, assessment instruments, and prompt banks, which were implemented through ongoing mentoring. These findings indicate that the integration of Deep Learning and AI effectively improves teacher professionalism and supports the transformation of learning in the era of artificial intelligence.